Techniques for identification, mapping and analysis of grasslands. Case study: Arad county - Mihai Simon; Loredana Copăcean; Luminiţa Cojocariu (Present Environment and Sustainable Development, 2022)
The development, in recent decades, of specific GIS and remote sensing techniques, facilitates the spatial analysis of the pastoral space and provides access to a huge volume of geospatial data. In this context, the purpose of the research is the mapping of the grasslands of Arad county and their analysis in correlation with the altitude and slope of the terrain. For Arad county, the grassland areas were identified and mapped, as follows: the Corine Land Cover database, 2018 edition, on a medium scale, was completed on the basis of orthophotoplans and cadastral plans at a scale of 1:10000, a process that obtained representation of grasslands on a large scale. The calculations show that 12% of the area of Arad county belongs to grasslands. The overlay analysis allowed the study of grasslands in correlation with other environmental factors, which can influence the floristic composition or their spatio-temporal dynamics. Thus, 89% of the grassland areas are located between 80.8 and 300 m altitude and 96% are located on slopes with an inclination below 15º. The application of GIS techniques in the research of grasslands in a given territory, offers the possibility of a holistic approach or for particular cases.